The Effect Of Fiscal Decentralisation Policy Implementation On Economic Development And Human Development Index On The Island Of Sumatra (2017-2023) - Handayani, R; Tahia, L (CERED Indonesia Institute, 2024)
This study aims to conduct an analysis of the Fiscal Decentralisation policy on the economic development of the island of Sumatra in 2017-2023. To estimate the economic development model between the Fiscal Decentralisation variables on the General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), Village Fund (DD) and Gross Regional Domestic Revenue (GRDP) per capita on the Human Development Index (HDI) of Sumatra Island in 2017-2022. Using time series and cross section data estimation methods within 7 years with common effect models (CEM), fixed effect models (FEM), and random effect models (REM). The estimation method used is Panel Data with the OLS model (Panel Ordinary Least Squares). The results of this study Testing the model using the chow test shows that the FEM model is more appropriate to use than the PLS model. Furthermore, the Hausman test shows that the FEM model is more appropriate to use compared to the REM model. Based on the validity test of the effect at a significance (?) of 0.05 based on the F statistical test, the DAU, DAK, DBH, DD, and PDRBKAP variables simultaneously have a significant effect on the human development index on the island of Sumatra in 2017-2023. The results of the determinant coefficient test (R2) show the magnitude of the R-square value of 0.936 or 93.69%, meaning that 93.69% of the variation in the Human Development Index variable is able to explain the DAU, DAK, DBH, DD, and GRDP KAP on the island of Sumatra, and the rest is explained by other variables that are not included in this research model.